Preparation of therapy-grade extracellular vesicles from adipose tissue to promote diabetic wound healing - Pan, Chuqiao; Xu, Peng; Zheng, Yi; Wang, Yikai; Chen, Chuhsin; Fu, Shibo; Liu, Zibo; Chen, Yahong; Xue, Ke; Zhou, Qimin; Liu, Kai (Frontiers in Bioengineering and Biotechnology, 2023)
Abstract Background: Treatment of diabetic wounds is a major challenge in clinical practice. Extracellular vesicles (EVs) from adipose-derived stem cells (ADSCs) have shown effectiveness in diabetic wound models. However, obtaining ADSC-EVs requires culturing vast numbers of cells, which is hampered by the need for expensive equipment and reagents, extended time cost, and complicated procedures before commercialization. Therefore, methods to extract EVs from discarded tissue need to be developed, for immediate application during surgery. For this reason, mechanical, collagenase-digestive, and constant in-vitro-collective methods were designed and compared for preparing therapy-grade EVs directly from adipose tissue. Methods: Characteristics and quantities of EVs were detected by transmission electron microscopy, nanoparticle tracking analysis, and western blotting firstly. To investigate the biological effects of EVs on diabetic wound healing, angiogenesis, proliferation, migration, and inflammation-regulation assays were then evaluated in vitro, along with a diabetic wound healing mouse model in vivo. To further explore the potential therapeutic mechanism of EVs, miRNA expression profile of EVs were also identified and analyzed. Results: The adipose tissue derived EVs (AT-EVs) were showed to qualify ISEV identification by NTA and western blotting and the AT-EVs yield from three methods was equal. EVs also showed promoting effects on biological processes related to diabetic wound healing, which depend on fibroblasts, keratinocytes, endothelial cells, and macrophages both in vitro and in vivo. We also observed enrichment of overlapping or unique miRNAs originate from different types of AT-EVs associated with diabetic wound healing for further investigation. Conclusion: After comparative analyses, a mechanical method was proposed for preparing immediate clinical applicable EVs from adipose tissue that would result in reduced preparation time and lower cost, which could have promising application potential in treating diabetic wounds.